2016
DOI: 10.1161/hypertensionaha.115.06398
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular Damage Mediates Relations Between Aortic Stiffness and Memory

Abstract: Aortic stiffness is associated with cognitive decline. Here, we examined the association between carotid-femoral pulse wave velocity and cognitive function and investigated whether cerebrovascular remodeling and parenchymal small vessel disease damage mediate the relation. Analyses were based on 1820 (60% women) participants in the Age, Gene/Environment Susceptibility – Reykjavik Study. Multivariable linear regression models adjusted for vascular and demographic confounders showed that higher carotid-femoral p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
94
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 118 publications
(98 citation statements)
references
References 40 publications
0
94
0
3
Order By: Relevance
“…Decreasing DBP from midlife to later life may be linked to cerebral hypoperfusion 33, 34. Decreasing DBP from midlife on is also a likely consequence of aortic stiffening, which contributes to cognitive decline 29, 35. We observed that the effect size of higher midlife PP levels on cognitive decline in later life was larger than that associated with higher SBP or with lower DBP.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Decreasing DBP from midlife to later life may be linked to cerebral hypoperfusion 33, 34. Decreasing DBP from midlife on is also a likely consequence of aortic stiffening, which contributes to cognitive decline 29, 35. We observed that the effect size of higher midlife PP levels on cognitive decline in later life was larger than that associated with higher SBP or with lower DBP.…”
Section: Discussionmentioning
confidence: 60%
“…A common cause may lead to both higher long‐term SBP variability and lower cognitive function. For example, adverse stressors (eg, psychosocial stress and sleep deprivation), large‐artery (aortic) stiffness, and lower socioeconomic status could lead to both increased long‐term SBP variability and lower cognitive function 19, 20, 28, 29…”
Section: Discussionmentioning
confidence: 99%
“…4 In this regard, elevated aortic stiffness and pulsatility are hypothesized to contribute, in part, to declines in cognitive performance with aging by promoting the development of subcortical white matter hyperintensities via increased cerebrovascular remodeling and resistance. 12,13 In addition, the link between age-related aortic stiffness and pulsatility with cerebral blood flow (CBF) and cerebrovascular reactivity, defined as the ability to augment brain blood flow in response to a vasodilatory stimulus, remains relatively unexplored. Experimentally, cerebrovascular reactivity is quantified by measuring cerebrovascular reserve (CVR) in response to a physiological or pharmacological stimuli, such as CO 2 or acetazolamide (ACZ), a carbonic anhydrase inhibitor.…”
mentioning
confidence: 99%
“…Earlier, there have been reports on repeated episodes of microvascular cerebral ischemia/hypoperfusion and impaired cerebral vasoreactivity amplified by blood pressure variability. In older adults from the Age, Gene/Environment Susceptibility (AGES)-Reykjavik Study, 8 cerebral microvascular remodeling and parenchymal damage (cerebrovascular resistance and WMH) were the inferred mechanisms that mediated the associations between cf-PWV and memory. There is a reasonable evidence that high blood pressure is mechanistically involved in CSVD.…”
Section: De Buyzere Stiff Arteries and Brain Aging In The Young 491mentioning
confidence: 99%